Prophylaxis against hepatitis A for travel. Issue 6726 (17th March 1990) - Moore, P; Oakeshott, P; Logan, J; Law, J; Harris, D M
Abstract : OBJECTIVE--To develop a rational practice policy for prophylaxis against hepatitis A for travellers to high risk areas. DESIGN--18 Month prospective study of consecutive patients who requested prophylaxis against hepatitis A. SETTING--Inner city general practice. SUBJECTS--104 Patients aged 15-61 (mean 30) assessed for risk factors for hepatitis A and put into groups depending on predictions from the risk factors of their immunity. MAIN OUTCOME MEASURES AND RESULTS--All patients were screened for antibody to hepatitis A virus. Of 52 patients with no risk factors 47 had no antibody and were thus susceptible to hepatitis A. All 27 patients with major risk factors (having been brought up in an endemic area or with a history of jaundice) were immune. Of 25 patients with minor risk factors (a history of previous travel in high risk areas, drug abuse, having lived in a squat or travelled rough, or having lived with someone who had jaundice) 12 were immune (p less than 0.001, chi 2 test). CONCLUSIONS--All travellers requesting prophylaxis against hepatitis A should be assessed for risk factors for previous exposure to hepatitis A. Those with no risk factors could be immunised with human normal immunoglobulin without screening. The remainder should be tested for hepatitis A antibody and those found to be susceptible should be immunised.